Influence of regional environmental management on citizen ecological behavior. Case study in the Department of Tacna, Peru - Cabrera-Huayhua, Juan Erik (2024)
Currently, most of the population does not have behaviors in favor of caring for the environment, which reduces the possibility of achieving sustainable development, which is mainly characterized by implementing actions that contribute to the rational use of   natural resources and minimize the effects of pollution, among others. The objective of the study was to determine the influence of regional environmental management on citizen ecological behavior in the department of Tacna. A sample of 384 citizens was considered, aged between 15 and 64 years who reside in the department of Tacna, who were selected at random, through, a stratified and proportional random sampling, distributed by province as follows: Tacna (357), Jorge Basadre (9), Candarave (10) and Tarata (8). The survey technique was used, through the application of two questionnaires: regional environmental management (16 items) and ecological citizen behavior (24 items). The findings of this research indicate that the ecological behavior of population is impacted by the implementation of activities that make up the environmental management promoted by the Regional Government of Tacna, in addition to each of the dimensions (regional plans and policies, regional system environmental, regional environmental policy and regional environmental commissions) have influence on the variable ecological citizen behavior.